Avaliação nasossinusal nos candidatos ao transplante hepático e a importância da tomografia computadorizada dos seios paranasais - Fernanda Vidigal Vilela Lima (2012)
The Federal University of Minas Gerais has one of the largest centers for liver transplantation in Brazil. As a result many patients are referred to the Department of Otorhinolaryngology prior to transplantation so that possible chronic infection sites (foci) may be detected. Because of the need for post-transplant immunosuppression, patients with chronic liver failure requiring transplantation must be free of infection to get active status on the transplantation list. Rhinosinusitis in post-transplant recipients can be complicated by life-threatening infections. There are no precise criteria for definitive screening of sinus foci among liver transplant patients. As part of an effort to identify patients at risk for later disease and detect occult infection pre transplant, our center routinely obtains pre transplant sinus scans. Our study evaluates the presence of chronic rhinosinusitis in pre-liver transplant patients and the value of paranasal computed tomography scans (CT). A total of 117 patients with chronic liver disease were evaluated in our service before getting active status in transplantation list. All of them were interviewed about nasal symptoms and had a complete head and neck examination. Diagnostic nasal endoscopy was part of the routine. Sinus CT scans were requested for every patient. Patients who were diagnosed with rhinosinusitis were treated with antibiotics before CT was performed. Findings on sinus CT were staged according to score established by Lund Mackay. This study also investigates the association of rhinosinusitis with MELD (Model for End-Stage Liver Disease) /PELD (Pediatric End-Stage Liver Disease) score, age, number of leucocytes, neutrophils and lymphocytes, albumin and hemoglobin. An incidence of 15,4% of rhinosinusitis was found, 10,3% was asymptomatic but CT suggested sinus disease. Patients with lower number of lymphocytes had higher risk to present this disease.